Is Team Formation Gender Neutral? Evidence from Coauthorship Patterns - Anne Boschini; Anna Sjögren (Research Institute of Industrial Economics (IFN), 2006)
We investigate if voluntary team formation is gender neutral. To this end, we model team formation as a random matching process influenced by the agents' preferences for team size and gender composition and derive how team formation depends on the gender ratio in the population of prospective team mates. We then test if the coauthorship pattern in articles published 1991-2002 in three top Economics journals is gender neutral, exploiting the variation in female presence across subfields of Economics. Our main finding is that gender sorting in coauthorship increases in the presence of women. In particular, we find that the gender gap in the propensity to coauthor with a woman increases in the presence of women in the subfield. We also find that women single author significantly more than men. These findings allow us to reject gender neutrality in team formation.
Keywords: A14; J16; J41; M50; 330; Team Formation; Gender Sorting; Coauthorship Patterns; Arbeitsgruppe; Bibliometrie; Ökonomen; Geschlecht; Entscheidung